A perspective on 6G: Requirement, technology, enablers, challenges and future road map - Ray, Partha Pratim (Journal of systems architecture, 2021)
Mobile network operators are at the verge of distribution and allotment of existing mobile communications with 5G. It is a high time that we should be focused on the forthcoming sixth generation (6G) networking. Though, it is mandated that 6G would leverage best of the existing network functions and cover an extended geographical range, we need to first understand the importance of 6G. In this article, we discuss about the vision of 6G and elaborate how it should look like with relevant elaborations. Key objective of this paper is to present analysis of the crucial requirements to develop 6G network infrastructure. We present a list of important networking and communication technologies that shall indeed play the vital role to design 6G. We also present how key enablers of 6G shall highlight their significance to emerge 6G. The article also presents important use case scenarios which may be overserved in the 6G era. Lastly, we find open research challenges and discuss way outs. Discussion about future road map designing concludes this literature.